Micro-Nano Bioactive Glass Particles Incorporated Porous Scaffold for Promoting Osteogenesis and Angiogenesis in vitro - Tian, Ting; Xie, Weihan; Gao, Wendong; Wang, Gang; Zeng, Lei; Miao, Guohou; Lei, Bo; Lin, Zhanyi; Chen, Xiaofeng (Frontiers in Chemistry, 2019)
Constructing the interconnected porous biomaterials scaffolds with osteogenesis and angiogenesis capacity is extremely important for efficient bone tissue engineering. Herein, we fabricated a bioactive micro-nano composite scaffolds with excellent in vitro osteogenesis and angiogenesis capacity, based on poly (lactic-co-glycolic acid) (PLGA) incorporated with micro-nano bioactive glass (MNBG). The results showed that the addition of MNBG enlarged the pore size, increased the compressive modulus (4 times improvement), enhanced the physiological stability and apatite-forming ability of porous PLGA scaffolds. The in vitro studies indicated that the PLGA-MNBG porous scaffold could enhance the mouse bone mesenchymal stem cells (mBMSCs) attachment, proliferation, and promote the expression of osteogenesis marker (ALP). Additionally, PLGA-MNBG could also support the attachment and proliferation of human umbilical vein endothelial cells (HUVECs), and significantly enhanced the expression of angiogenesis marker (CD31) of HUVECs. The as-prepared bioactive PLGA-MNBG nanocomposites scaffolds with good osteogenesis and angiogenesis probably have a promising application for bone tissue regeneration.